Nutritional habits and emotional states in COVID-19 time - Torres Huamani, Yanina Milagros (2021)
Healthy lifestyles reduce the likelihood of contracting degenerative diseases, however; during the COVID-19 pandemic, there were difficulties in sustaining them. Overweight and obesityare associated with eating behaviors that affect health and consequently alter immune responses that weaken defenses, increasing the likelihood of contracting this disease. This article aimed to determine the nutritional and emotional consequences of sedentary lifestyles caused by SARS-CoV-2. A systematic search was conducted of publications in the databases of SciELO, Dialnet, Science Direct, Pub Med, the World Health Organization (WHO), Association of Obesity, British Medical Journal, American Society for Microbiology and Infectious Diseases Society of America, on the consequences and causes of obesity and its aggravating factors. In parallel, 51 people were surveyed to identify the conditions they faced during confinement. Respondents reported significant changes in their daily lives, mainly in terms of food shopping, i.e. the availability of healthy food, physical inactivity due to isolation, and a deterioration in their physical condition. A healthy lifestyle is a priority to prevent future illnesses. This work can serve as a reference for future research to try to identify those factors that impact lifestyles  due to COVID-19 confinement.